Local geometry of equilibria and a Poincaré-Bendixson-type theorem for holomorphic flows - Kainz, Nicolas; Lebiedz, Dirk (Topology Proceedings, 2024)
In this paper, we explore the local geometry of dynamical systems x=F(x) with real time parameterization, where F is holomorphic on connected open subsets of C R^2. We describe the geometry of first-order equilibria. For equilibria of higher orders, we establish an equivalent condition for "definite directions", allowing us to reverse the implication in Theorem 2 of Chapter 2.10 in [Differential equations and dynamical systems, Lawrence Perko (1990)] under the additional condition of holomorphy. This enables the geometric construction of a finite elliptic decomposition. We derive a holomorphic Poincaré-Bendixson-type theorem, leading to the conclusion that bounded non-periodic orbits are always homoclinic or heteroclinic.